1978
DOI: 10.3109/03009747809095648
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Penicillamine and Gold Treatment in Early Rheumatoid Arthritis

Abstract: In a series of 100 adult patients with definite rheumatoid arthritis of at most 3 years' duration and with no previous penicillamine, gold or systemic corticosteroid treatment, 50 patients were treated with D-penicillamine and 50 with gold for one yar. The dose of penicillamine was 600 mg daily. Sodium aurothiomalate was given 50 mg weekly up to a total of 13 mg/kg and thereafter 50 mg once a month. In both treatment groups a statistically significant decrease in the number of painful and/or swollen joints, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…2), the patients' anaemia failed to respond significantly to penicillamine treatment whereas previous reports have indicated significant improvement during treatment. 25 32 The concurrent aspirin therapy may be responsible for this lack of response. However, an enteric coated preparation was used, minimising gastric bleeding, and the dose was reduced over the 24-week period.…”
Section: Discussionmentioning
confidence: 99%
“…2), the patients' anaemia failed to respond significantly to penicillamine treatment whereas previous reports have indicated significant improvement during treatment. 25 32 The concurrent aspirin therapy may be responsible for this lack of response. However, an enteric coated preparation was used, minimising gastric bleeding, and the dose was reduced over the 24-week period.…”
Section: Discussionmentioning
confidence: 99%
“…These effects which are in part statistically significant are paralleled by a drop in the ESR and by clinical improvement. Similar effects on immunological parameters are usually seen only in patients treated with gold salts or D-penicillamine (9).…”
Section: Discussionmentioning
confidence: 61%
“…The so-called long-term or specific agents, such as gold salts (9), D-penicillamine (91, and antimalarial drugs, are capable of suppressing rheumatoid inflammation. However, their use is often limited by severe side effects.…”
mentioning
confidence: 99%
“…A total of 29 interventions among 132 randomized clinical trials (RCTs) represented by 130 publications (mean [range], 71.0% [27.0%-100%] females in studies; mean [range] of ages in studies, 53 [36-70] years) were identified, which included 13 260 patients with rheumatoid arthritis. The number of studies with measured outcomes was 118 studies for TJC, 116 studies…”
Section: Resultsmentioning
confidence: 99%
“…For our primary analysis of all 132 studies (represented by 130 publications) we used the most frequently reported outcome, TJC. This included imputed TJC values for studies that did not measure TJC (eMethods 5 in Supplement 1), denominated TJCi.…”
Section: Methodsmentioning
confidence: 99%